Disruption of human papillomavirus 16 E6 gene by clustered regularly interspaced short palindromic repeat/Cas system in human cervical cancer cells - Yu, Lan (Onco Targets Ther, 2014)
High-risk human papillomavirus (HPV), especially HPV16, is considered a main causative agent of cervical cancer. Upon HPV infection, the viral oncoprotein E6 disrupts the host tumor-suppressor protein p53, thus promoting malignant transformation of normal cervical cells. Here, we used the newly developed programmable ribonucleic acid-guided clustered regularly interspaced short palindromic repeat (CRISPR)/Cas system to disrupt the HPV16 E6 gene. We showed that HPV16 E6 deoxyribonucleic acid was cleaved at specific sites, leading to apoptosis and growth inhibition of HPV16-positive SiHa and CaSki cells, but not HPV-negative C33A or human embryonic kidney 293 cells. We also observed downregulation of the E6 protein and restoration of the p53 protein. These data proved that the HPV16 E6 ribonucleic acid-guided CRISPR/Cas system might be an effective therapeutic agent in treating HPV infection-related cervical malignancy.